Somatic signaling mediated by fs(1)Yb is essential for germline stem cell maintenance during Drosophila oogenesis. - King, F.J.; Lin, H. (Development, 1999)
Drosophila oogenesis starts when a germline stem cell divides asymmetrically to generate a daughter germline stem cell and a cystoblast that will develop into a mature egg. We show that the fs(1)Yb gene is essential for the maintenance of germline stem cells during oogenesis. We delineate fs(1)Yb within a 6.4 kb genomic region by transgenic rescue experiments. fs(1)Yb encodes a 4.1 kb RNA that is present in the third instar larval, pupal and adult stages, consistent with its role in regulating germline stem cells during oogenesis. Germline clonal analysis shows that all fs(1)Yb mutations are soma-dependent. In the adult ovary, fs(1)Yb is specifically expressed in the terminal filament cells, suggesting that fs(1)Yb acts in these signaling cells to maintain germline stem cells. fs(1)Yb encodes a novel hydrophilic protein with no potential signal peptide or transmembrane domains, suggesting that this protein is not itself a signal but a key component of the signaling machinery for germline stem cell maintenance.